CFD modelling and anfis development for the hydrodynamics prediction of bubble column reactor ring sparger / Mohammad Pourtousi - Mohammad , Pourtousi (2016)

(untitled)
A detailed understanding of the interactions between gas bubbles and the liquid phases in bubble column reactors (BCR), which enhance the heat and mass transfer and chemical reactions, will greatly assist in the design and optimization of the reactor. Despite of wide researches on industrial BCRs, there are still many design aspects of the reactor and sparger (e.g., sparger types, position and velocity, as well as orifice size of the sparger) that require further investigation. A proper selection of BCR and spargers for different industries would greatly improve BCR efficiency and productivity. In addition, an accurate prediction of BCR hydrodynamics with less computational efforts is a major concern in the design and optimization process. In this study, the effect of ring sparger diameters, superficial gas velocities and number of sparger holes on the flow pattern and gas dynamics in BCR have been investigated. The two-phase Eulerian-Eulerian method embedded in the Commercial Computational Fluid Dynamic software, ANSYS CFX, V14 has been adopted to study the macroscopic hydrodynamics inside a cylindrical BCR. Relevant literature on experimental and numerical results and empirical correlations has been used for validation. Changing the ring sparger diameter and the superficial velocity has a significant effect on the results in comparison to that of the case of the different number of sparger holes. The influence of microscopic parameters such as orifice size, inlet gas velocity, distance between orifices and number of orifices on a single bubble formation, rising, as well as bubble coalescence process are studied using the Volume of Fluid (VOF) method which is embedded in ANSYS FLUENT, V14. In addition, an experimental work has been carried out to validate some of the CFD cases investigated and also to study the effect of inlet flowrate and orifice size on bubble detachment from an orifice. iv An increase in the number of orifices (more than two) resulted in faster bubble detachment from the orifices. This also lead to the production of large bubbles with non-uniform shapes. By determining the specific distance between orifices resulted in bubble formation without coalescence and a uniform size and shape of bubbles. For the first time, the Adaptive Neuro Fuzzy Inference System (ANFIS) model has been developed to predict the microscopic and macroscopic parameters of BCR hydrodynamics. Some of the CFD results from the previous chapters have been used for the development, training, testing and validation of the ANFIS model. The developed ANFIS model is used to predict the liquid flow pattern and gas dynamics for different ring sparger diameters and BCR heights. ANFIS model is also developed for the prediction of the bubble formation from an orifice and to investigate the bubble rise characteristics. Some limitations are found in ANFIS model and this is discussed. As a conclusion, ANFIS method can be employed to predict microscopic and macroscopic results for various operational conditions of BCRs. Unlike the CFD implementation process, ANFIS model has the capability to predict the required results fast and requires less computational effort in providing a non-discrete (continuous) result.